The Central Medial Thalamus Serves as a Critical Hub for Preserved Arousability During Dexmedetomidine Sedation - Yunyun Zhang; Sa Wang; Haonan Li; Xinxin Zhang; Dan Wang; Ye Wang; Weichao Bai; Zefei Zhang; Guangchao Zhao; Tingting Gu; Hailong Dong; Qianzi Yang (Neuroscience Bulletin, 2026)
Dexmedetomidine (DEX) induces a distinct state of “arousable sedation,” yet the neural circuits that sustain arousal capacity remain unclear. Here, we identified that 40 μg/kg DEX produced sedation from which animals could be transiently aroused by tactile stimulation of the back, whereas 100 μg/kg induced deeper, unresponsive sedation. Functional mapping revealed selective activation of the central medial thalamus (CMT). Fiber photometry further confirmed that DEX dose-dependently and selectively activated glutamatergic neurons in the CMT while simultaneously suppressing activity in other thalamic regions. Chemogenetic inhibition of CMT glutamatergic neurons deepened DEX sedation and impaired tactile‑stimulation-induced arousal following administration of 40 μg/kg DEX, whereas activation of CMT glutamatergic neurons under a high-dose DEX (100 μg/kg) attenuated sedation and restored tactile responsiveness. Together, these results establish the CMT as a critical thalamic node for maintaining arousal capacity during DEX sedation.